In-situ transformation of a perovskite oxide from irregular particles into nanosheets for active and durable solid oxide fuel cell cathodes - Shuai Ma; Shengli Pang; Xudong He; Hao Lou; Kaijie Xu; Yaozheng Qian; Fang Yang; Yi Zhuang; Xuyao Luo; Lianxu Xu; Yifei Gao; Peijie Zhang; et al. (Journal of Materiomics, 2025)
Solid oxide fuel cells (SOFCs) are of paramount importance for developing green and sustainable energy systems. However, achieving stable nanoscale cathode catalysts under their typically high operating temperatures, normally exceeding 600 °C, remains a significant challenge. By introducing a small amount of RuCl3 into the cathode slurry, an in-situ transformation of the PrBaCo2O5+δ cathode catalyst can be induced from submicrometer-scale irregular particles into nanosheets during SOFC operation. These nanosheets feature a RuO2-modified surface layer, resulting in substantial improvements in both catalytic activity and operational durability. At 750 °C and 0.7 V, SOFCs employing conventional cathode catalysts exhibit a 6.1% degradation in power density over 110 h, while those employing the nanosheet-structured catalysts achieve an 11.9% increase, ultimately stabilizing at a high-power density of 0.75 W/cm2. This work presents a simple and scalable strategy for constructing high-performance nanocatalysts and deepens our theoretical understanding of catalyst nanostructuring for SOFC applications.